Trajectories of loneliness among older women and men: Variation by sexual identity? - Lam, Jack; Campbell, Alice (My University, 2022)
The aim of this study is to contribute to the literature on variation in later-life outcomes by sexual identity. Drawing on the Iridescent Life Course framework, we examined differences in loneliness trajectories, and tested the roles of social connectedness and support, and socioeconomic and health statuses in explaining any observed disparities. Using growth models, we analysed 19 years of data (2001-2019) from adults aged 50 years and older from the Household, Income and Labour Dynamics in Australia Survey (n=5,500 individuals), where a question on sexual identity was asked twice in the study. One percent of our sample reported a change in their sexual identity, which we grouped with individuals who reported as bisexual. Our sample comprised of 45.3% heterosexual men, 52.2% heterosexual women, 0.6% gay men, 0.6% lesbian women, 0.6% bisexual-plus men, and 0.6% bisexual-plus women. We found bisexual-plus men were vulnerable to loneliness as they aged. This group had the highest levels of loneliness at age 50, and differences compared with heterosexual men persisted over time. Loneliness of bisexual-plus men increased steeply from age 70. Socioeconomic and health statuses did not explain the increased loneliness of older bisexual-plus men. Lower social support and connectedness partly accounted for these disparities. Findings are discussed with regards to existing research and theories on social disadvantage and resilience over the life course. We expand knowledge on factors explaining loneliness and how it varies in women and men by sexual identity.
The Gernontologist
Keywords: Disadvantage, adversity and resilience; Gender; Identity